Comportamiento agronómico y valoración nutricional de la asociación de matarratón (gliricidia sepium) con pasto tanzania (panicum maximun), y pasto mulato (brachiaria híbrido). - Velasquez Morales, Pedro Adán (2012)
In the property "María" of the Technical State University of the canton Quevedo, located in the km 7 of the Road Quevedo. The Connection, county of Ríos, county of Ríos was determined the agronomic "Behavior and nutritional value of the association of Matarratón (Gliricidia sepium) with grass Tanzania (Panicum maximun to cultivate TANZANIA) and Mulatto (hybrid Brachiaria)" grass in different states of maturity, where they took as objectives to analyze the agronomic behavior of the gramineous-leguminous associations and to carry out the analyses bromatológicos to determine the nutritional value, using a design of complete blocks at random (DCA). In the simple effect of the grass, the association Matarratón with grass Tanzania obtained the best indexes in the variables root (233,10 g) weight, forage (192,38 g) weight, weight of leaves (40,20 g), shaft (65,35 g) weight and relationship leaves aérea:parte radicular (1,06). And in the simple effect of the ages the highest results in almost all the variables excepting the relationship leaves aérea:parte radicular they corresponded to the age of 80 days. In the interaction of the associations for the ages, the best indexes in root (464,1 g) weight, forage (334,95 g) weight, weight of leaves (70,1 g), shaft (107,2 g) weight and relationship leaves aérea:parte radicular (1,53 kg), they register to the 80 and 110 days in the association of Matarratón with the grass Tanzania; and the best relationship hoja:tallo (1,03) with the association of Matarratón with grass Mulatto to the 110 days. The protein greater levels were obtained with the association of Matarratón with grass Tanzania to the 80 and 140 days with the 8,72 and 8,50%. And the lowest fiber level is reported in the association of Matarratón with grass Mulatto to the 140 days with 7,90%. For the composition microbiológica at 80 140, the tall populations in actinomicetes, celulolíticos and fixers of N asimbiótico showed up with the association of Matarratón and Mulatto grass. The bigger than colonization percentage to the 80 and 140 days showed up in the association of Matarratón with the grass Tanzania. For the obtained results you confirmed the outlined hypotheses: "The nutritious value of the gramineous-leguminous association Matarratón with grass Tanzania for the two court ages will be superior" and "The gramineous-leguminous association Matarratón (Gliricidia sepium) but Clitoria (Clitoria sepium) with grass Tanzania (Panicum maximun to cultivate TANZANIA) will show the biggest production of biomass in the different states of maturity."